Iron homeostasis and its interaction with prolyl hydroxylases. - Mole, D (2010)
The ability of iron to accept or donate electrons, coupled with the ability of oxygen to act as an electron acceptor, renders both elements essential to normal cellular biology. However, these same chemical properties allow free iron in solution to generate toxic free radicals, particularly in combination with oxygen. Thus, closely interwoven homeostatic mechanisms have evolved to regulate both iron and oxygen concentrations at the systemic and the cellular levels. Systemically, iron levels are regulated through hepcidin-mediated uptake of iron in the duodenum, whereas intracellular free-iron levels are controlled through iron-regulatory proteins (IRPs). Cardiorespiratory changes increase systemic oxygen delivery, whereas at a cellular level, many responses to altered oxygen levels are coordinated by hypoxia-inducible factor (HIF). However, the mechanisms of iron homeostasis also are regulated by oxygen availability, with alterations in both hepcidin and IRP activity. In addition, many genes involved in iron homeostasis are direct targets of HIF. Furthermore, HIF activation is modulated by intracellular iron, through regulation of hydroxylase activity, which requires iron as a cofactor. In addition, HIF-2alpha translation is controlled by IRP activity, providing another level of interdependence between iron and oxygen homeostasis.